Grid Economics and Business Models: 5th international workshop, GECON 2008, Las Palmas de Gran Canaria, Spain, August 26, 2008 ; proceedings - Neumann, Dirk (Springer, 2017)
This volume constitutes the refereed proceedings of the 5th International Workshop on Grid Economics and Business Models, GECON 2008, held in Las Palmas de Gran Canaria, Spain, August 2008.